1990
DOI: 10.1002/dir.4000040406
|View full text |Cite
|
Sign up to set email alerts
|

The role of perceived risk in mail order catalog shopping

Abstract: The purpose of this article is to review the marketing literature concerning perceived risk and to offer a conceptual application of this literature to the mail order catalog shopping purchase situation. Five specific types of perceived risk are presented and discussed in relation to risk reduction techniques applicable to each. The author's conceptualizations concerning perceived risk are an attempt to promote academic empirical research, as well as to enhance practitioners' understanding of their o w n curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
10

Year Published

1992
1992
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(65 citation statements)
references
References 33 publications
(49 reference statements)
0
53
0
10
Order By: Relevance
“…And studies have shown that sensory attributes (such as fabric and garment fits, color, etc.) are important to shoppers [78], but may be difficult to evaluate online [79]. This suggests that the S individual, who places more importance on their sensory feedback, is likely to perceive less ''ease of use'' associated with a virtual store than the N individual.…”
Section: Sensing (S) or Intuitive (N) Individuals And Virtual Storesmentioning
confidence: 95%
“…And studies have shown that sensory attributes (such as fabric and garment fits, color, etc.) are important to shoppers [78], but may be difficult to evaluate online [79]. This suggests that the S individual, who places more importance on their sensory feedback, is likely to perceive less ''ease of use'' associated with a virtual store than the N individual.…”
Section: Sensing (S) or Intuitive (N) Individuals And Virtual Storesmentioning
confidence: 95%
“…Grewal et al, (1994) studied the six dimensions or components of perceived risk from different angles. McCorkle (1990) has suggested the resource risk, which M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 10 takes place from the loss caused by the dishonest behavior of the sellers. But, authors have considered PR from the consumers' point of view of returning their used items.…”
Section: Pr On Rimentioning
confidence: 99%
“…Following these, McCorkle (1990) added a dimension of time risk that reflects the potential time loss between order and fulfilment. Security and/or privacy issues were regarded as an important concern in online shopping (Crespo et al, 2009).…”
Section: Facets Of Perceived Riskmentioning
confidence: 99%